Clinical study of emergency obstetric hysterectomy in tertiary care center - Yannam, Rishitha Reddy; Thirumaran, Harshini; Meghana, Kanchibhotla; Vasantha Lakshmi, G. N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The aim of study was to assess the frequency, demographic features, reasons, and outcomes for both the mother and fetus linked to emergency obstetric hysterectomy. Methods: We conducted a hospital based retrospective cohort study, between January 2016 to November 2023. A comprehensive study was conducted on 36 instances of emergency obstetric hysterectomy (EOH) at Sri Ramachandra institute of Higher Education and Research (SRIHER), Chennai, within the Department of Obstetrics and Gynecology. The study encompassed pregnant women delivering from 28 completed weeks of gestation to term, specifically those who underwent hysterectomy either during the intrapartum period or within the puerperium due to complications arising during childbirth. Results: The incidence of EOH in our study was 22 per 1,00,000 following vaginal delivery and 196 per 1,00,000 following caesarean section. The overall incidence was 106 per 1,00,000 deliveries. Morbidly adherent placenta (39%) was the most common indication followed by Atonic postpartum hemorrhage (36%) and Placenta previa with placenta accreta (20%). Anemia (67%) emerged as the most prevalent maternal complication, with fever (30%) following closely behind. Conclusions: In situations where traditional surgical methods prove ineffective and immediate access to interventional radiology is unavailable, a well-balanced approach to EOH can be life-saving. Our study underscores the significance of EOH in the coming years, given the increasing probability of both cesarean sections and multiple pregnancies.